Pemanfaatan Kulit Pisang Sebagai Bahan Baku Pembuatan Pektin - Dwinna Rahmi; Siti Agustina (Jurnal Kimia dan Kemasan, 1999)
One of the solution of waste problem is converted them to become a product which can give benefit for human being. Banana peel is a raw material for producing pectin. From five kind 's banana peel which is used the use of ambon 's banana peel produced the higher content of low metoksil pectin, i. e 3 - 5 %, followed by raj a serai 's banana peel, i. e 1 %, low metoksil . The use of acid as an extraction agent will influence the result